Andosols property dynamics under intensive tea cultivation in West Java: Implications for sustainable management - Rachmat Abdul Gani; Bambang Hendro Trisasongko; Budi Mulyanto; Sukarman Sukarman; Edi Yatno; Rufaidah Qonita Muslim; Haikal Caesa Prayudi; Heppy Suci Wulanningtyas; Destika Cahyana (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2026)
Despite its significant economic value, tea cultivation in Indonesia is experiencing a continuous decline in plantation area, primarily due to changes in land use. Soil fertility degradation and reduced yields present a significant threat to the long-term sustainability of tea production. A comprehensive understanding of the dynamic nature of tea plantation soil properties is essential for developing sustainable land management strategies aimed at enhancing and maintaining the productivity and sustainability of healthy tea cultivation. This study investigates the properties of Andosols formed from andesite tuff in a heavily managed tea plantation in Cisarua, Bogor, West Java, Indonesia. Four vertical soil profiles and ten composite soil samples were collected from depths of 0-20 cm and 20-40 cm across varying tea vigor and slope class gradients in block plantations. The ongoing production of tea on Andosols has led to significant chemical decline, evidenced by decreased organic matter, increased acidity, reduced cation exchange capacity, and compromised andic properties. The observed rise in base saturation primarily indicates a reduction in CEC, rather than an improvement in fertility. The observed patterns indicate progressive soil weathering and reduced resilience in monoculture systems. Restorative management, which encompasses the incorporation of organic matter and a balanced nutrient supply, is essential for maintaining soil functionality and securing long-term tea productivity. This article synthesizes key findings regarding soil properties, anthropogenic impacts, and strategies for sustainable management. Understanding these dynamics is crucial for optimizing good soil management practices and enhancing tea productivity in volcanic areas.